Determining the mutation bias of favipiravir in influenza using next-generation sequencing - Goldhill,DH; Langat,P; Xie,H; Galiano,M; Miah,S; Kellam,P; Zambon,M; Lackenby,A; Barclay,W (Journal of Virology, 2019)
Favipiravir is a broad-spectrum antiviral drug that may be used to treat influenza. Previous research has identified that favipiravir likely acts as a mutagen but the precise mutation bias that favipiravir induces in influenza virus RNAs has not been described. Here, we use next-generation sequencing (NGS) with barcoding of individual RNA molecules to accurately and quantitatively detect favipiravir-induced mutations and to sample orders of magnitude more mutations than would be possible through Sanger sequencing. We demonstrate that favipiravir causes mutations and show that favipiravir primarily acts as a guanine analogue and secondarily as an adenine analogue resulting in the accumulation of transition mutations. We also use a standard NGS pipeline to show that the mutagenic effect of favipiravir can be measured by whole genome sequencing of virus.IMPORTANCE New antiviral drugs are needed as a first line of defence in the event of a novel influenza pandemic. Favipiravir is a broad-spectrum antiviral which is effective against influenza. The exact mechanism of how favipiravir works to inhibit influenza is still unclear. We used next-generation sequencing (NGS) to demonstrate that favipiravir causes mutations in influenza RNA. The greater depth of NGS sequence information over traditional sequencing methods allowed us to precisely determine the bias of particular mutations caused by favipiravir. NGS can also be used in a standard diagnostic pipeline to show that favipiravir is acting on the virus by revealing the mutation bias pattern typical to the drug. Our work will aid in testing whether viruses are resistant to favipiravir and may help demonstrate the effect of favipiravir on viruses in a clinical setting. This will be important if favipiravir is used during a future influenza pandemic.